Mobile work in crisis. Issue 2 (2nd July 2016) - Petersen, Katrina; Büscher, Monika
Abstract: This paper explores some of the complexities and practices of the massively distributed and mobile work of crisis response. The analysis is motivated by our work of applying insights from social science studies to socio-technical and organisational innovation in crisis management. Insights from ethnographic observations of physically mobilising a multi-agency emergency response are contrasted with a study of troubles in mobilising data for multi-agency and cross border collaboration in crisis management. The analysis shows that a situated interactive order of trust as well as reflexive social and material practices that make for productive rapports are critical for good collaboration. We explore how a deeper understanding of such practices can shed light upon difficulties encountered around supporting interoperability based in immaterial mobile work of networked collaborations.